Pelaksanaan E-Court Menurut Perma Nomor 3 Tahun 2018 Tentang Administrasi Perkara Di Pengadilan Secara Elektronik Dan E-Litigation Menurut Perma Nomor 1 Tahun 2019 Tentang Administrasi Perkara Dan Persidangan Di Pengadilan Secara Elektronik (Studi Di Pengadilan Negeri Di Indonesia) - Retnaningsih, Sonyendah; Nasution, Disriani Latifah Soroinda; Velentina, Rouli Anita; Manthovani, Kelly (UI Scholars Hub, 2020)
The process of resolving cases at a trial is not always carried out conventionally ie the parties come directly to the trial but can be done online. This is marked by the launch of the e-court application on July 13, 2018. With the launch of the e-court application, the Supreme Court has moved towards electronic justice which will fundamentally change the practice of litigation services in the courts. Since the issuance of Supreme Court Regulation No. 1 of 2019 concerning Administrative of Cases and Trials in Electronic Courts on August 19, 2019, the Supreme Court Regulation No. 3 of 2018 concerning Administration of Cases in Electronic Courts was declared revoked and no longer valid. This PERMA Number 1 of 2019 perfected PERMA Number 3 of 2018 so that now not only case registration can be done online or known as e-court but the trial can also be conducted electronically namely e-litigation.